1. Преобразуем уравнение:
4х^2 + 12х + 12/х + 4/х^2 = 47;
4(х^2 + 2 + 1/x^2) - 8 + 12(х + 1/х) - 47 = 0;
4(х + 1/x)^2 + 12(х + 1/х) - 55 = 0.
2. Замена:
х + 1/x = t;
4t^2 + 12t - 55 = 0;
D/4 = 6^2 + 4 * 55 = 36 + 220 = 256 = 16^2;
t = (-6 ± 16)/4;
t1 = (-6 - 16)/4 = -22/4 = -11/2;
t2 = (-6 + 16)/4 = 10/4 = 5/2.
3. Обратная замена:
х + 1/x = t;
х^2 + 1 = tx;
х^2 - tx + 1 = 0;
1) t = -11/2;
х^2 + 11/2 * x + 1 = 0;
2х^2 + 11x + 2 = 0;
D = 11^2 - 4 * 2 * 2 = 121 - 16 = 105;
x1/2 = (-11 ± √105)/4;
2) t = 5/2;
х^2 - 5/2 * x + 1 = 0;
2х^2 - 5x + 2 = 0;
D = 5^2 - 4 * 2 * 2 = 25 - 16 = 9;
x = (5 ± √9)/4 = (5 ± 3)/4;
x3 = (5 - 3)/4 = 2/4 = 1/2;
x4 = (5 + 3)/4 = 8/4 = 2.
ответ: (-11 ± √105)/4; 1/2; 2.
х²-10х+11=0
D=(-(-10))²-4×1×11=100-44=66
x1=(-(-10)-√66)/2×1=(10-8,12)/2=1,88/2=0,94
x2=(-(-10)+√66)/2×1=(10+8,12)=18,12/2=9,06
x=0
y=0²-10×0+11
y=11
(0,94;0), (9,06;0) и (0;11).
2) х=0
у=0²-3×0+4
у=4
у=0
х²-3х+4=0
D=(-(-3))²-4×1×4=9-16=-7
D<0, так как дискриминант меньше нуля, решений нет.
(0;4)
3) х=0
у=0³-3×0
у=0
у=0
х³-3х=0
х(х²-3)=0
х1=0
х²-3=0
х²=3
х2=-√3
х3=√3
(0;0), (-√3;0) и (√3;0)